PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA INDUSTRIFARMASI DI BEI PERIODE 2008-2010 - Asnita . (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2013)
The Stock Price as firms valueindicatoris influence by fundamental factors basically was influenced by business firms financial ratio such as Current Ratio (CR), Total Asset Turn Over (TATO), Debt to Assets Ratio (DAR), Return on Equity (ROE), Earning Per Share (EPS), dan Price Earning Ratio (PER ).This research uses secondary data that collect from Pharmacy Industries in periode of 2008-2010 year.Based on research results, the entire independent ratio influences Stock Price significantly. It is shows by the value R2, where 88, 20 percent variation of Stock Price is could be explained by finantial ratios.Furthermore, partially ROE and EPS has significant effect. Keywords : Business performance, price stock, pharamacy industries.